2012
DOI: 10.1128/jb.01694-12
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Bacillus pumilus BA06, a Producer of Alkaline Serine Protease with Leather-Dehairing Function

Abstract: Bacillus pumilus BA06 was isolated from the proteinaceous soil and produced an extracellular alkaline protease with leatherdehairing function. The genome of BA06 was sequenced. The comparative genome analysis indicated that strain BA06 is different in genome from the other B. pumilus strains, with limited insertions, deletions, and rearrangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Dehairing enzymes from Bacillus sp. have also been reported in the literature [14][15][16]. Furthermore, a recent patent proposed a concrete mixture of dehairing enzymes from B. subtilis and B. cereus with sodium carbonate, caustic soda, and thioglycolic acid [17].…”
Section: Introductionmentioning
confidence: 96%
“…Dehairing enzymes from Bacillus sp. have also been reported in the literature [14][15][16]. Furthermore, a recent patent proposed a concrete mixture of dehairing enzymes from B. subtilis and B. cereus with sodium carbonate, caustic soda, and thioglycolic acid [17].…”
Section: Introductionmentioning
confidence: 96%
“…To date, 22 genomes of strains and isolates of B. pumilus have been sequenced, including isolate BA06 [55], the progenitor of strain SCU11. Nevertheless, studies focusing on the extracellular proteome and related secretory systems of B. pumilus remain inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…According to the genome sequence (Zhao et al, 2012), the strain BA06 possesses several genes encoding extracellular protease homologous to these genes (aprE, epr, vpr, wprA, aprX) in the B. subtilis strain 168, all of which were predicated to encode proteases with a secretary signal peptide (data not shown), and their products were detected in the extracellular proteome of BA06 (Yu, 2012). Therefore, real-time PCR was applied to analyze their transcriptions under salt stress.…”
Section: Transcription Of Protease-encoding Genes Under Salt Stressmentioning
confidence: 99%
“…Since genome sequencing revealed that B. pumilus BA06 possesses several putative genes encoding extracellular proteases (Zhao et al, 2012), zymogram analysis has been per- Figure 2. Repression of extracellular protease production by Bacillus pumilus BA06 following salt stress both in fermentation broth (A) and on milk-containing agar plates (B).…”
Section: Zymogram Analysis Of Extracellular Proteases Under Salt Stressmentioning
confidence: 99%
See 1 more Smart Citation